ALTERNATIVE FUELS – A BOON FOR FUTURE GENERATIONS - Kaur, Gurkirat (SCHOOL SCIENCE, 2010)
This concern and words of apprehension regarding conventional petroleum products has been starting the people all over the world since a decade. There is a growing anxiety due to general environmental, economic, and geopolitical matters of sustainability of the petroleum products. Also the prices of the fossils fuels have been upsurging day-by-day. The only solution to these problems is the identification and usage of the alternative fuels in industry, transportation and in economy of the world.